Tren Berhijab di Kalangan Anak Muda: Studi Komparatif pada Siswi SMA/MA/SMK di Pekanbaru - Euis Karmila (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2020)
This paper analyzes the use of hijab which is a trend now among teenagers in high school. This article will explain the differences between public schools and Islamic based schools. This study is important to see how the role of hijab trends in schools is used by students. Specifically, this article will address the following questions. Why girls hijab? What kind of model is used by schoolgirls like? What is the role of the school to educate students in the use of the hijab. Methodologically, the data for this article is sourced from field study research in several high school / vocational schools located in Pekanbaru. The author will ask several questions relating to the discussion that the writer will do. This article is analyzed with a number of literatures that are relevant to this research topic. The results of the study show that students who attend public schools attend schools that use the hijab. And in using hijab, it's very different. In the role of the school also differs between public schools and Islamic based schools. Starting in terms of regulations to how to educate students to use the hijab.